The clinical spectrum and outcome of dermatological conditions in patients admitted to dermatology wards of Groote Schuur Hospital-Cape Town South Africa - Ashour, Emad (Division of Dermatology, 2022)
Background: Groote Schuur Hospital (GSH) Division of Dermatology receives many referrals from local clinics and hospitals. Some of these patients are admitted to the dermatology wards for diagnosis and/or management. It is important to look at the spectrum and outcome of these patients who are admitted to dermatology wards at the hospital, to inform policy. Objectives: To characterise the spectrum of dermatological conditions requiring admission, to determine the outcome and to describe the factors that may influence the outcome of dermatological conditions in patients admitted to the dermatology wards at Groote Schuur Hospital in South Africa. Methods: This research employed descriptive retrospective analysis to describe the dermatology inpatients who were admitted to dermatology wards at Groote Schuur Hospital over the period January 2017 to December 2017. Results: There were a total of 120 admissions to Groote Schuur Hospital Dermatology wards in 2017. Of these, 89 (74.1%) were new admissions and 31 (25.8%) re-admissions. The most frequent diagnosis was drug reaction (27.5%), followed by psoriasis (23.3%), eczema (17.5%), and bullous disease (10%). Less common indications for admission were infections, lupus erythematosus, scabies, ulcers, pyoderma gangrenosum and cutaneous small-vessel vasculitis. The outcome of the admission was usually favorable. Conclusions: The most common diagnoses on admission were drug reactions, psoriasis, eczema, and bullous diseases. The generally favorable outcomes would support the future use of inpatient care for people with severe skin disorders.